A ideia de felicidade em Bauman: um contraponto à tradição. - Silva, Jaires Firmino da (2022)
Through “The Art of Life”, by Zygmunt Bauman, we seek to understand what happiness is and if, in fact, it is possible in a liquid modern society. The Polish philosopher brings, in his work, an exposition of philosophical and sociological ideas. Contrasting with the philosophical tradition from the cuttings of the main authors of each philosophical period, ranging from Ancient to Contemporary Philosophy. In addition, this work aims to signal his thinking in an attempt to a better comprehension of happiness throughout History. Based on the theme from above, it will be discussed whether there are continuity relations or ruptures between Bauman's concept of happiness and the History of happiness, since thinking afterwards and about the Philosophy of happiness in postmodernity are challenged by the own culture and dominant of a liquid society, more and more rapidly, more and more prone to instantaneous changes, the result of an increasingly globalized world, which projects in time ephemeral and fleeting feelings. Thus, the author's work provokes us to fight more and more for better themes shown and that are often divergent, but often the philosophical debates seen in academies, today, reserved for academic self-help books, today, reserved for academic self-help books.